"It is better to be safe 100 times than dead once."—Mark Twain. Issue 4 (4th October 2018) - Edwards, Victor; Study, Karen
Abstract : A number of major process incidents during the 1980s led the Occupational Safety and Health Administration (OSHA) to promulgate the process safety management regulation in 1992 (1). Those incidents and the anticipation of the new OSHA regulations energized the South Texas Section of American Institute of Chemical Engineers (AIChE), and eight other organizations including the AIChE Center for Chemical Process Safety (CCPS), to create the first process plant safety symposium (PPSS) in 1992. The symposium was held in Houston as a low‐cost and convenient training forum for the large community of engineers and scientists at regional chemical process plants and refineries. Approximately 700 people attended. Subsequently, the PPSS has evolved to become one of the four main tracks in AIChE's Global Congress on Process Safety. In the intervening years, 18 PPSSs have been held. The unique focus of these symposia has been on practices, perspectives, methods, and tools to improve process safety at the plant level. This article, presented at the 20th PPSS, reviews examples of how progress in process safety has been facilitated by these symposia. The article concludes with a look to the future for needed advances in process safety. © 2018 American Institute of Chemical Engineers Process Saf Prog 37: 452–458, 2018